Shifting Social Norms and Adolescent Girls' Access to Sexual and Reproductive Health Services and Information in a South African Township. (May 2022) - Gillespie, Bronwen; Balen, Julie; Allen, Haddijatou; Soma-Pillay, Priya; Anumba, Dilly
Despite policy on adolescent sexual and reproductive health (SRH) services and education, teen pregnancies remain common in South Africa. Social norms and cultural resistance are a well-documented challenge for SRH program implementation in South Africa, and beyond. To gain insight on the complex picture of adolescents' access to SRH information and services in a peri-urban township, we explored this topic from a diversity of perspectives, carrying out 86 interviews to capture perceptions of adolescents, their parents, community members, and health professionals. Our research shows that despite the taboo nature of the issue of adolescent SRH, individual positions on adolescent access to SRH services and information are shifting and diverse, and are influenced by factors other than cultural norms. This research serves as a reminder to avoid simplistic reference to "culture" as a way of explaining health-related behaviors and people's responses to health challenges.